Design and Investigation of Outer Rotor Permanent Magnet Flux Switching Machine for Downhole Application - Rajesh Kumar; Erwan Sulaiman; Mahyuzie Jenal; Laili Iwani Jusoh; Fatihah Shafiqah Bahrim (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Permanent magnet flux switching machine (PMFSM) is a joint venture of switch reluctance machine (SRM) and permanent magnet synchronous machine (PMSM). It has become a prominent research topic for various applications because of robust rotor structure, high torque and power densities but few were developed for downhole applications mainly due to harsh environmental conditions. Formerly, most of developed PMFSMs for downhole applications were mainly concentrated on inner-rotor type design, and difficult to find research work on outer-rotor configuration. Therefore, this paper introduces the design and investigation of PMFSM with outer-rotor configuration for downhole application. Primarily, the geometric topology of proposed design is described in detail. Then, the no load and load analysis are implemented in order to investigate the initial performance of the proposed design.